Independence of Judges and Public Opinion - Meliyani Sidiqah (Sociological Jurisprudence Journal, 2023)
The research article titled "Independence of Judges and Public Opinion" delves into the intricate relationship between the freedom of judges and public opinion, two intangible yet impactful forces that shape the judicial landscape. The freedom of judges and public opinion are two things that cannot be seen, but both can be reflected. This freedom seems an absolute power in making decisions, even though this freedom still has limitations. Unfortunately, we cannot find the judge's standing point in the decision because the judge did not provide his arguments, making it difficult to identify whether the judge was influenced by public opinion or not. This article examined the relationship between the judge’s independence and the judge’s power in making decisions and the effects of public opinion on the judge’s independence. This article is a normative juridical research with interdisciplinary method research by using perspectives from other scientific disciplines that used to support discussions related to the problem which still use the law as a standpoint. This article discussed not only from a normative perspective, but other aspects such as sociology, culture, and psychology. The result of this research, the relationship between the judge’s independence and the judge’s power in making decisions must be maintained by the judge’s integrity, and public opinion as a long-life problem could affect the judges through pressure. There must be a regulation that orders the judges to provide the arguments according to the case which can be assessed by anyone, and surveillance according to the decision that has to give feedback to the judges itself. Besides, there must be an accountability system for the supervision of judges related to the contents of the decision, to society, people, organization, and state.